STATUS SOSIAL EKONOMI DAN PERAN TENAGA KESEHATAN TERHADAP KUNJUNGAN ANTENATAL CARE MASA PANDEMI COVID-19 DI BPM HENI AFRINA KOTA PEKANBARU TAHUN 2021 - Tengku NINGSIH (STIKes Al-Insyirah Pekanbaru, 2022)
Background: Indonesia is currently experiencing a national disaster, namely COVID-19 so that maternal and neonatal health services are one of the health services affected by access and quality, limiting services to almost all routine services including maternal and neonatal health services. Factors causing pregnant women to be less obedient in performing ANC regularly and on time, namely: lack of knowledge about ANC, busyness, low socioeconomic level, lack of husband's support, lack of convenience for maternal services, poor medical care, lack of trained personnel and drugs soul savior. Porpose: to find out the relationship between socioeconomic status and the role of health workers in ante natal care visits during the Covid-19 pandemic. Method: This type of quantitative research with correlation studies (correlation study). The population and sample of all pregnant women who came for a pregnancy check at BPM “H” Pekanbaru City in December 2021 were 31 respondents. Sampling using total sampling. The instrument used was a questionnaire, using the Chi Square statistical test p˂0.05, the data was processed using the SPSS application. Results: Chi Square test analysis of the role of health workers p value of 1,000 and socio-economic status p value of 0.810. Conclusion: There is no significant relationship between the role of health workers and socioeconomic status on ante natal care visits, it is hoped that health workers will improve counseling, increase counseling and promotion activities continuously with updated knowledge and multimedia development in delivering materia